Empowering metropolitan regions through new forms of cooperation - Otgaar, Alexander H. J. (EURICUR series., 2008)
This insightful book analyzes the development of cross-border and cross-sector partnerships in a number of European cities and regions. Including, amongst others, Copenhagen, Budapest, Helsinki, Munich and Catalonia, these case studies shed light on the factors determining the success or failure of the coalition-forming process.